ON AGE OF NAZIMOVSKAYA AND KHASAN FORMATIONS IN THE PALEOGENE SUCCESSION OF SOUTHWESTERN PRIMOR'E - Pavlyutkin B.I.; Petrenko T.I.; Nevolina S.I.; Kutub-Zade T.K. (My University, 2006)
Materials of previous studies and new original geological and paleobotanic data are used to substantiate synchronism (late Eocene) of the Khasan and Nazimovskaya formations, the key stratigraphic units of the Paleogene in Primor'e. Coal-bearing sediments of the units rest upon early-middle Eocene volcanics (Kraskino rhyolite tuffs, Zaisanovka basaltic andesites) being overlain by the lower Fatash Subformation of the lower Oligocene with flora of the Kraskino type. The Ust'-Davydovskaya Formation of the Rechnoi Peninsula (outskirts of Vladivostok) is the most probable analogue of the Khasan (=Nazimovskaya) Formation. © MAIK "Nauka/Interperiodica" 2006.
Keywords: EOCENE; FOSSIL FLORA ASSEMBLAGES; OLIGOCENE; PRIMOR'E REGION; STRATIGRAPHY; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Eocene